Agroforestry As An Alternative To Facing Climate Change In The Community, Ponorogo Regency - Marti Winarni; Anang Susanto; Dobashi Nunes (International Journal of Science and Environment (IJSE), 2023)
Changes in the seasons on earth can cause problems for farmers in determining the planting and harvesting seasons. Management of forest areas with good agroforestry strategy by utilizing it to produce food in partnership with the community effectively inhibits the increasing rate of climate change. The agroforestry implementation strategy with the social and economic conditions of the community is also used to explore how far the impact of climate change on changes in current conditions. . The research aims to formulate strategies that must be developed to adapt to climate change. The AHP results show that the economic aspect has a priority weight of 0.89, the environmental factor has a 0.39 weight and the organizational part has a 0.26 weight. Work steps of the parties involved and priorities in the short and long term. For the parties involved, it is necessary to prioritize its implementation so that the community's economy can run according to expectations. The short-term priorities are training on climate change information and its impacts, group management and administration, entrepreneurship, marketing, and intensive mapping of CSR opportunities. In the long term, the government, academic can provide facilitators and assistance for technology transfer in dealing with climate change.